81.2k views
19 votes
Can someone please answer this fast! thanks

Can someone please answer this fast! thanks-example-1
User James Pack
by
5.2k points

1 Answer

5 votes

Answer:

The choice C.


{x}^{ (5)/(2) }

Explanation:


\frac{ {x}^(3) }{ √(x) } = \frac{ {x}^(3) }{ {x}^{ (1)/(2) } } = {x}^(3) * {x}^{ - (1)/(2) } \\ = {x}^{3 * - (1)/(2) } = {x}^{ (5)/(2) }

Or ;


\frac{ {x}^(3) }{ √(x) } = {x}^(2) √(x) = {x}^(2) * {x}^{ (1)/(2) } \\ = {x}^{2 + (1)/(2) } = {x}^{ (5)/(2) }

User Yurkevich
by
4.9k points